Artful Inquiry in the E-learning Journal (LEARNing Landscapes, 2016)
E-learning is transforming the learning landscape. This paper focuses on photomedia participatory inquiry in an e-feed learning culture. It harnesses the bene ts of artful inquiry and elaborates on interactive re ective opportunities when using participatory research methods. Student e-learning journal examples and the teacher re ective voice demonstrate how artful inquiry accommodates critical and re ective actions for new creative outcomes. The methods described and analyzed may have relevance to educators considering applying multi-semiotic learning approaches within e-learning journals as digital platforms become central to digital learning and communication of ideas.
Keywords: E-learning; artful inquiry; digital learning; photomedia participatory inquiry; participatory research